Penggunaan Media Papan Ular Tangga untuk Meningkatkan Pemahaman Numerasi Bagi Siswa Kelas III di SDK Bejo - Oli, Maria Anjelina; Dhiu, Konstantinus Dua; Ngura, Elisabeth Tantiana; Sayangan, Yohanes Vianey (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to improve the ability of numeracy in mathematics learning by using the snakes and ladders board for 3rd grade students in SDK Bejo. This type of research is a Class Action Research (PTK) involving 19 students consisting of 9 male students and 9 ability students. The method used in this research is the method of data collection using tests. This study was conducted with pre cycle, cycle 1 and Cycle 2. The results showed that the use of media Board snakes and ladders can significantly improve the ability of numeracy summation 1-100 in students tingakt phase B. The use of snakes and ladders board media in mathematics learning with the topic of solving simple 1-100 is stated to increase after using snakes and ladders board media from pre-cycle to Cycle 1 by 13.16% and obtaining an average pre-cycle score of 53.68% to Cycle 1 an average of 66.84% or in the good category. From cycle I to Cycle II experienced an average increase of 86.84%. Whereas, classically there is an increase from cycle I to Cycle II which is equal to 100% of the determination of 70%. This indicates that the use of snakes and ladders board Media is very effective in improving numeracy skills in children aged 8-9 years.